O saldo da balança comercial entre Brasil e EUA: uma estimação das suas elasticidades preço e renda por meio do método VAR e VEC - Lima, Lincoln Diogo (2012)
This dissertation aims at analyzing empirically, by means of estimates of price and income elasticities, the behavior of the trade balance between Brazil and the USA, between january 1990 and october 2011. The theoretical approaches of Elasticities and Absorption provide the theoretical relations for determinants of trade balance, allowing the construction of a workable structure for empirical research. Empirical studies on the subject shows that, recently, the form of data aggregation and development of new econometric methods, considered by many researchers more appropriate for variables that are not sure about its exogeneity, drove the emergence of new work on the trade balance. The methodology used is the technique of Johansen s multivariate cointegration and vector autoregressive models (VAR) and vector error correction (VEC). It was concluded that the real exchange variables, brazilian income, income U.S., trade balance bilateral Brazil-United States has a long term relationship and expected signs, as economic theory postules, and income elasticities, especially in the U.S, are elastic and more important than the elasticity of the real exchange (inelastic) to explain the trade balance in the long run between the two countries. This indicates that to occur a reversal in the pattern of deficit trade balances of the last three years, the slowdown in income growth in Brazil and / or the resumption of US income growth is more important than a devaluation. Nevertheless, the Marshall-Lerner condition is satisfied and the J curve phenomenon not